2023
DOI: 10.3390/su15118997
|View full text |Cite
|
Sign up to set email alerts
|

Smallholder Farmers’ Climate Change Adaptation Strategies in the Ethiopian Rift Valley: The Case of Home Garden Agroforestry Systems in the Gedeo Zone

Aberham Darge,
Jema Haji,
Fekadu Beyene
et al.

Abstract: Smallholder farmers who rely on home garden agroforestry are experiencing significant impacts from climate change. To mitigate these effects, it is crucial for farmers to have access to various adaptation strategies. This study collected data from 384 randomly selected respondents in 18 kebeles over three districts, using descriptive statistics and a multivariate probit model to evaluate the factors influencing smallholder farmers’ decisions on their adaptation strategies against climate change. In Ethiopia’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Thus, when a household's income increases by one unit, the likelihood of implementing improved crop varieties, inorganic fertilizers, and mixed farming increases by 0.891, 1.302, and 1.250 times, respectively. Likewise, previous studies have shown that households with higher income levels are better able to perform adaptation options quickly than those with lower income levels(Adimassu & Kessler, 2016;Asayehegn et al, 2017;Darge et al, 2023).…”
mentioning
confidence: 86%
“…Thus, when a household's income increases by one unit, the likelihood of implementing improved crop varieties, inorganic fertilizers, and mixed farming increases by 0.891, 1.302, and 1.250 times, respectively. Likewise, previous studies have shown that households with higher income levels are better able to perform adaptation options quickly than those with lower income levels(Adimassu & Kessler, 2016;Asayehegn et al, 2017;Darge et al, 2023).…”
mentioning
confidence: 86%
“…Climate change has caused extreme weather to occasionally affect protected fields, not to mention HFG sites without shelter. Typhoons, frosts, hailstorms, and heat injuries have become commonplace, making it difficult for HFG to operate outdoors and ultimately leading to a failure to improve food self-provisioning (Du Toit et al, 2022;Darge et al, 2023).…”
Section: Weak Light and Changing Weather Conditionsmentioning
confidence: 99%